The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12988/ams.2014.47508
|View full text |Cite
|
Sign up to set email alerts
|

The mathematical models of gas transmission at hyper-pressure

Abstract: Different approaches to the modeling of thermodynamic processes in a gas flow at hyper-pressure are discussed and their equivalence is proved for any form of equation of state. The article presents arguments in favor of the approach in which temperature and density are chosen as independent thermodynamic variables and equation of sate is written in one of its analytical forms, for example, in the form of Redlich-Kwong equation of state. Explicit analytical expressions are obtained for the dependences of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The model of thermodynamic processes in gas flow at hyper-pressure (with inlet pressure up to 21 MPa) was investigated [8]. The Redlich-Kwong, Soave, Peng-Robinson, GERG (the European Gas Research Group) equations of state were considered.…”
Section: Modelling Of Thermodynamic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of thermodynamic processes in gas flow at hyper-pressure (with inlet pressure up to 21 MPa) was investigated [8]. The Redlich-Kwong, Soave, Peng-Robinson, GERG (the European Gas Research Group) equations of state were considered.…”
Section: Modelling Of Thermodynamic Processesmentioning
confidence: 99%
“…h, c, δ are constants in the Redlich-Kwong equation of state (10) determined by a given chemical composition of a gas mixture [8];c v in equations (11) and (12) is the specific heat of an ideal gas (including ideal gas mixtures).…”
Section: Modelling Of Thermodynamic Processesmentioning
confidence: 99%
“…Various analytical and numerical methods were developed for solving complete or reduced options of linear and nonlinear quasi-one-dimensional equations of pipelines transporting compressible or low-compressible media [12][13][14][15][16][17][18][19]. The analysis showed that few publications are devoted to studying changes in the fluid momentum in inclined pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays lattice Boltzmann method (LBM) [2], [9], [11], [12] is considered as a powerful method for the solution of different fluid dynamics problems [3], [13], [14]. The method is based on the solution of the system of kinetic equations instead the system of the equations of hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%